2022
DOI: 10.7759/cureus.21459
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Infective Endocarditis Complicated With Coronary Artery Embolization

Abstract: Infective endocarditis is a multisystem and potentially fatal disease. Systemic embolization is a relatively common complication, the spleen and central nervous system being the most frequent sites for septic emboli formation. Coronary artery septic embolization is extremely uncommon and its management remains controversial.We present the case of a 50-year-old male diagnosed with mitral valve infective endocarditis complicated with spleen and central nervous system embolization, who developed acute myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…ACS that complicates infectious endocarditis is a rare complication, with an incidence of 2.9% and a mortality rate which can reach up to 64% [ 29 , 31 ]. Usually, coronary embolism occurs in the first 15 days of the disease [ 35 ]. Our literature review indicates that, in patients with large vegetations and prosthetic valves, embolic phenomena are often recurrent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACS that complicates infectious endocarditis is a rare complication, with an incidence of 2.9% and a mortality rate which can reach up to 64% [ 29 , 31 ]. Usually, coronary embolism occurs in the first 15 days of the disease [ 35 ]. Our literature review indicates that, in patients with large vegetations and prosthetic valves, embolic phenomena are often recurrent.…”
Section: Discussionmentioning
confidence: 99%
“…3.1.5. Embolic Events from Endocarditis on the Right-Side Valves IE on the right side is more commonly associated with IVDA, intravenous catheters, and intracardiac devices [20,35].…”
Section: Pathogens Involved In Septic Embolization From Endocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern was the timing of the surgery. Recent studies have shown better outcomes with early surgery (within three days of brain infarction) than delayed surgery [ 1 ]. However, in the current case, we performed the surgery six days after the brain infarction, which resulted in no exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis (IE) is a devastating disease caused by Staphylococcus aureus . IE occurs in approximately 3-10/100,000 people [ 1 ]. Its predisposing risk factors include intravenous drug use, valve prolapse, prosthetic valve replacement, intracardiac defects, and hemodialysis.…”
Section: Introductionmentioning
confidence: 99%